Method optimization for the determination of total arsenic and selenium content in fish by ICP-MS preceding to speciation studies. - Inês, Coelho (2012)
The present work constitutes the first task of a three year project that aims for the optimization and validation of a methodology to determine the total concentration of Arsenic (As) and Selenium (Se) and its species in fish products by using HPLC-ICP-MS. Prior to initializing speciation studies the method for determination of total arsenic and selenium content was optimized. For that purpose reference materials (DORM-3 and BCR-627) were used as well as spiked samples. Sample preparation using closed vessel microwave digestion was optimized by trying several nitric acid/peroxide hydrogen ratios and varying time and temperature conditions. Results were evaluated by calculating the extraction yield of trace elements from matrix and trueness of reference materials results. Parameters such as repeatability, reproducibility and linearity were evaluated using real samples such as tuna fish and sole. ICP-MS conditions were optimized on a daily basis and calibration solutions were prepared fresh every day. Recovery percentages indicated that digestion conditions are complex and food matrix dependent. The use of the correct internal standards, in this case Yttrium and Rhodium were chosen, as well as its concentration is essential for obtaining accurate results. Also fundamental is matching as much as possible the concentration of nitric acid used in the preparation of calibration solutions to the one from test solutions after microwave digestion. Recovery using commercial calibrants and reference materials was the best parameter to assess the adequacy of the analytical procedure. The obtained results were supported by good laboratory performance in collaborative studies. In future work methods for identifying and quantifying arsenic and selenium species by using HPLC-ICP-MS will be developed.